Penerapan Strategi Pembelajaran Berdiferensiasi Berorientasi Kebutuhan Belajar untuk Meningkatkan Minat Belajar Matematika - Haslianti Haslianti; Sartika Arifin; Nursafitri Amin; Nurfadilah Mahmud (FKIP Universitas Mataram, 2025)
The low interest in learning mathematics among students is a common problem in education. Students tend to lack enthusiasm and motivation in participating in mathematics learning due to conventional teaching methods that have not accommodated the diversity of student characteristics. This study aims to improve the mathematics learning interest of seventh-grade students at SMP Negeri 6 Tinambung through the implementation of differentiated learning strategies. This research is a classroom action research using the Kemmis and McTaggart model design in 2 cycles consisting of planning, action, observation, and reflection. The research subjects were 22 seventh-grade students at SMP Negeri 6 Tinambung. The results of data analysis showed that the average percentage of students' mathematics learning interest questionnaire increased from 71.23% to 79.83% (high category) with an increase of 12.07%. The average percentage of teacher activity increased from 90% to 98.33% (Very Good category) with an increase of 8.33%, and the average percentage of student activity increased from 86% to 97% (Very Good category) with an increase of 12.79%. Based on these results, it can be concluded that the implementation of differentiated learning strategies can improve the mathematics learning interest of seventh-grade students at SMP Negeri 6 Tinambung.